7. SINIF FEN VE TEKNOLOJİ DERSİ "İNSAN VE ÇEVRE" ÜNİTESİNİN İŞBİRLİKLİ ÖĞRENME MODELİYLE ÖĞRETİMİNİN ÖĞRENCİ BAŞARISINA ETKİSİ (ELAZIĞ İLİ ÖRNEĞİ) - AKSOY, ŞEYMA BARATA (Fırat Üniveristesi, 2017)
Bu çalışmada işbirlikli öğrenme modeline dayalı Jigsaw yönteminin 7.sınıf öğrencilerinin akademik başarılarına olan etkileri araştırılmıştır. Uygulama 7.sınıf Fen ve Teknoloji dersi "İnsan ve Çevre" ünitesinin işlenmesi kapsamında yapılmıştır. Çalışma deney ve kontrol grupları kullanılarak gerçekleştirilmiştir. Deney grubuna İşbirlikli öğrenme, kontrol grubuna sorucevap-düz anlatım uygulanmıştır. Uygulama sonunda İşbirlikli öğrenme açısından sınırda anlamlılıktan söz edilebilmektedir.

In this study, the effects of the Jigsaw method based on the cooperative learning model on the academic achievements of the 7th grade students were investigated. The practice was held within the scope of "Human and Environment" unit of 7th grade Science and Technology course. "Science and Technology Preliminary Information Test" prepared by the researcher was applied to both experiment and control group in order to form groups heterogeneously before the application. Then, at the beginning of the application, the researcher's "Science and Technology Academic Achievement Test" was applied to both of the groups. The unit was processed via the "Cooperative Learning" with Jigsaw method to experimental group while the control group was processed by using the straight expression method. During the application, the subject distribution and time in the unit were made to be equal to both the experiment and the control group. At the end of the application, the "Science and Technology Academic Achievement Test" was applied as a final test. The obtained data were analyzed statistically by SPSS technique (t test) and then it was observed that there was a meaningful difference between the experimental group students who applied cooperative learning method and the control group with the straight expression method in academic achievement
Human and environment" unite of 7th grade science and technology course; cooperative learning models' effects on the student performance (Sample of Elazığ province)
Keywords: Eğitim ve Öğretim